2020
DOI: 10.3390/ijerph17082797
|View full text |Cite
|
Sign up to set email alerts
|

Hope, Loneliness and Sense of Coherence among Bereaved Parents

Abstract: Coping with the loss of a child is a challenging and difficult experience that disrupts the lives of the surviving parents and the fabric of the family. Our goal is to identify the factors that help bereaved parents cope with this loss and introduce hope and future perspectives into their lives. Our sample consisted of 81 parents (30 fathers and 51 mothers), who completed questionnaires on the following topics: family climate, loneliness, sense of coherence and hope. In addition, interviews were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Various studies have documented the relations between hope and loneliness. In a recent study on bereaved parents, increased levels of loneliness predicted lower levels of hope (Einav & Margalit, 2020). In another study, both hope and loneliness were found to mediate the effect of stress on subjective vitality (Satici, 2020).…”
Section: Loneliness and Hopeful Thinkingmentioning
confidence: 93%
“…Various studies have documented the relations between hope and loneliness. In a recent study on bereaved parents, increased levels of loneliness predicted lower levels of hope (Einav & Margalit, 2020). In another study, both hope and loneliness were found to mediate the effect of stress on subjective vitality (Satici, 2020).…”
Section: Loneliness and Hopeful Thinkingmentioning
confidence: 93%
“…A stronger SOC is associated with a better perception of one's own health, especially in the mental area (Eriksson & Lindström, 2006 ). It is the personal resilience component that enables the continuation of activity, the identification of goals, and the progression towards achievement (Einav & Margalit, 2020 ). Individuals with a high sense of coherence are able to evaluate the world around them accurately (comprehensibility); are aware that their actions are worth the work and effort they expend (meaningfulness); and actively cope with stressors and remain confident that they have adequate resources to manage them (manageability) (Antonovsky, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…This is what distinguishes between people with a stronger and weaker SOC. The former will search hard for those coping resources which are potentially available to him or her; the latter are more likely to give up ( Einav & Margalit, 2020 ; Sagy, 1994 ).…”
Section: Introductionmentioning
confidence: 99%